PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS IV SDN 105350 PERBARAKAN - Bella Puspita; Arrini Shabrina Anshor; Nurmairina; Dara Fitrah Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Study This aiming For develop diorama learning media for increase interest Study student Grade IV Elementary School. Research This is type study development Research and Development using the ADDIE model with five stages , namely Analysis, Design, Development, Implementation, And Evaluation. Technique data collection used in study This that is observation , interview , questionnaire And documentation . Instrument And technique data analysis used in study This is questionnaire or the questionnaire given to a number of reviewer expert , namely reviewer expert materials , media experts , teacher responses and response interest Study student . Score obtained​ from validation expert material which is 92%. Media experts are 80%. The teacher's response was 96%. Response interest Study student which is 85.75. From the score the can it is said that the diorama learning media for increase interest Study student developed grade IV elementary school is already